Digital resilience in Chinese adolescents: a portrayal of the current condition, influencing factors, and improvement strategies - Qi, Chunlin; Yang, Nanchang (Frontiers in Psychiatry, 2024)
Inroduction Digital resilience is an important skill for adolescents in the digital age, but there is a lack of valid and reliable assessment methods. This study aimed to develop and validate a digital resilience questionnaire for Chinese adolescents based on the Digital Resilience Framework proposed by the UK Children’s Internet Safety Council Methods This study employed a mixed research design, combining quantitative and qualitative data collected and analyzed. Over a six-month period (January to June 2023), a questionnaire was distributed to 12,208 adolescents from 10 high schools and 16 middle schools, with in-depth interviews performed with 10 of the participants. Results The study revealed that Chinese adolescents digital resilience levels are slightly higher than average (M = 3.5038 > 3.5), but there is still potential for development, particularly in active learning. Additionally, a variety of characteristics influencing adolescents digital resilience were discovered, including gender, family residency, whether they are only children, grade level, the number of digital devices used per week, and the length of hours spent online daily. Discussion This study developed and verified a digital resilience questionnaire for Chinese adolescents, which may be used to assess and improve their digital skills and well-being in the digital age. The study also identified various variables and themes that influence digital resilience, which can be used to navigate educational initiatives and policy. However, this study's shortcomings included a cross-sectional design, self-reported data, and cultural distinctiveness. Future research could address these limitations by undertaking a longitudinal study, utilizing numerous data sources, and contrasting different cultural contexts.